Instruments to Measure Patient Satisfaction with Comprehensive Medication Management Services: A Scoping Review Protocol - Lorayne Caroline Resende; Mariana Martins Gonzaga do Nascimento; Mariana Michel Barbosa; Cristiane de Paula Rezende; Laís Lessa Neiva Pantuzza; Edna Afonso Reis (Pharmacy, 2022)
Comprehensive medication management (CMM) is the service offered within the clinical practice of pharmaceutical care, which has the objective to optimize pharmacotherapeutic outcomes. Patient satisfaction is a multidimensional construct that points to the quality of the health services offered and the degree to which the patients’ expectations and needs are met. The evaluation of the level of patient satisfaction is a key indicator to support decisions and to improve the quality of the service provided. This study aims to describe the protocol for a scoping review to map the instruments to measure patient satisfaction with CMM services and compare them according to their development characteristics and the applicability of patient-reported outcome measures. The literature search will be conducted using the scoping review methodology, proposed by the Joanna Briggs Institute and the PRISMA Extension for Scoping Reviews (PRISMA-ScR) method. The results will be presented in two sessions: (1) description of the search strategy; and (2) the characteristics of the satisfaction instruments, number of items and questions related to the conceptual model, content validity, construct validity, reliability, score/interpretation, and respondent burden. This review will shed light on the available satisfaction measurement instruments, allowing existing gaps to be identified for future research.